Dietary Depletion of Milk Exosomes and Their MicroRNA Cargos Elicits a Depletion of miR-200a-3p and Elevated Intestinal Inflammation and Chemokine (C-X-C Motif) Ligand 9 Expression in Mdr1a−/− Mice. Issue 12 (31st October 2019) - Wu, Di; Kittana, Hatem; Shu, Jiang; Kachman, Stephen D; Cui, Juan; Ramer-Tait, Amanda E; Zempleni, Janos
ABSTRACT: Background: Exosomes transfer regulatory microRNAs (miRs) from donor cells to recipient cells. Exosomes and miRs originate from both endogenous synthesis and dietary sources such as milk. miR-200a-3p is a negative regulator of the proinflammatory chemokine (C-X-C motif) ligand 9 (CXCL9). Male Mdr1a −/− mice spontaneously develop clinical signs of inflammatory bowel disease (IBD). Objectives: We assessed whether dietary depletion of exosomes and miRs alters the severity of IBD in Mdr1a −/− mice owing to aberrant regulation of proinflammatory cytokines. Methods: Starting at 5 wk of age, 16 male Mdr1a −/− mice were fed either milk exosome– and RNA-sufficient (ERS) or milk exosome– and RNA-depleted (ERD) diets. The ERD diet is characterized by a near-complete depletion of miRs and a 60% loss of exosome bioavailability compared with ERS. Mice were killed when their weight loss exceeded 15% of peak body weight. Severity of IBD was assessed by histopathological evaluation of cecum. Serum cytokine and chemokine concentrations and mRNA and miR tissue expression were analyzed by multiplex ELISAs, RNA-sequencing analysis, and qRT-PCR, respectively. Results: Stromal collapse, gland hyperplasia, and additive microscopic disease scores were (mean ± SD) 56.7% ± 23.3%, 23.5% ± 11.8%, and 29.6% ± 8.2% lower, respectively, in ceca of ERS mice than of ERD mice ( P  < 0.05). The serum concentration of CXCL9 was 35.0% ± 31.0% lower in ERS mice than in ERD mice ( P  < 0.05). Eighty-seven mRNAs were differentially expressed in the ceca from ERS and ERD mice; 16 of these mRNAs are implicated in immune function. The concentrations of 4 and 1 out of 5 miRs assessed (including miR-200a-3p) were ≤63% lower in livers and ceca, respectively, from ERD mice than from ERS mice. Conclusions: Milk exosome and miR depletion exacerbates cecal inflammation in Mdr1a −/− mice.